2019
DOI: 10.1016/j.ijid.2018.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Towards achieving the fast-track targets and ending the epidemic of HIV/AIDS in Ethiopia: Successes and challenges

Abstract: Background: Ethiopia has adopted the global plan to end the epidemic of HIV/AIDS. The aim of this study was to assess the progress made towards achieving this plan. Methods: A review and analysis of national population-based surveys, surveillance, and routine programme data was executed. The data analysis was conducted using Excel 2016 and Stata 14 (StataCorp LP, College Station, TX, USA). Results: Between 2011 and 2016, the number of HIV-related deaths dropped by 58%, while that of new HIV infections dropped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 25 publications
4
32
2
Order By: Relevance
“…Other models focusing on India and the USA have also failed to demonstrate 90% HIV incidence reduction by 2030 if Fast-Track targets are met [35,36]. Our finding are also consistent with analysis of population-based surveys, surveillance, and routine program data used in Ethiopia that demonstrated that for HIV testing, ART, viral suppression, and AIDS-related deaths Fast-Track targets will be reached, but not targets for reductions in new HIV infections based on progress made between 2011 and 2016 [37].…”
Section: Discussionsupporting
confidence: 77%
“…Other models focusing on India and the USA have also failed to demonstrate 90% HIV incidence reduction by 2030 if Fast-Track targets are met [35,36]. Our finding are also consistent with analysis of population-based surveys, surveillance, and routine program data used in Ethiopia that demonstrated that for HIV testing, ART, viral suppression, and AIDS-related deaths Fast-Track targets will be reached, but not targets for reductions in new HIV infections based on progress made between 2011 and 2016 [37].…”
Section: Discussionsupporting
confidence: 77%
“…The missed ART refill appointments could be due to either busy work schedules, lack of transport fares or could even have been used to mask either perceived or experienced stigma [44]. These challenges are likely to affect more people, as increasing numbers are diagnosed as living with HIV as universal treatment access is rolled out in the effort to reach the UNAIDS 2020 targets [45].…”
Section: Discussionmentioning
confidence: 99%
“…Ethiopia is one of the HIV high burden countries that has adopted the 90-90-90 fast-track targets (Joint United Nations Programme on HIV/AIDS, 2014). A recent study indicated that progress towards achieving the 2020 targets are on track: 79% PLHIV know their status, 90% PLHIV are on ART, and 88% of PLHIV have suppressed viral loads (Assefa et al, 2019). However, the prevalence of HIV and incidence of new infections remain high (Girum et al, 2018).…”
Section: Introductionmentioning
confidence: 99%